KONSEP FITRAH MANUSIA DALAM PSIKOLOGI ISLAM: INTEGRASI PERSPEKTIF AL-QUR’AN DAN TEORI PSIKOLOGI MODERN - Nikmah Rochmawati; Fathin Khoirunnisa; Iis Nur Milah Abhari (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2026)
The study explores the concept of fitrah within Islamic psychology and its integration with the theories of humanistic psychology. The findings revealed that despite the similarities between both perspectives in recognizing the innate potential of humans, both differ in their ultimate purposes, where humanism is anthropocentric, emphasizing individual autonomy, whereas fitrah is theocentric, aiming at fulfilling the role of human beings as 'abdullah and khalifah. The implications of this study suggest the development of an integrated psychological framework that incorporates spiritual dimensions into human development